Preparation method of ammonia synthesis catalyst and synthesis method of ammonia
By using SiC as a support and performing thermal shock treatment in Joule heating device, an efficient Ru/SiC catalyst was prepared, which solved the stability and cost problems of the existing ammonia synthesis catalyst in the ammonia synthesis process, and achieved low temperature and low pressure conditions efficient ammonia production under the
Patent Information
- Application Number
- CN202411492316.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
AI Technical Summary
The existing ammonia synthesis catalysts have problems of methanation, metal sintering and poor mechanical strength during the synthesis of ammonia, which limits its further promotion and application, and the existing improved methods increase process complexity and cost.
SiC is used as a support and thermal shock treatment is performed through a Joule heating device to create SiC surface defects to stabilize Ru particles, and Ru/SiC catalyst is obtained by ultrasonic dispersion and drying, achieving its efficient ammonia synthesis under low temperature and low pressure conditions.
It improves the activity and service life of the catalyst, reduces costs, simplifies the process, has potential industrial application prospects, and maintains high-efficiency ammonia generation rate over a long period of time.
Smart Images

Figure CN119236984A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ammonia preparation, and in particular to a method for preparing an ammonia synthesis catalyst and a method for synthesizing ammonia. Background Art
[0002] Ammonia (NH3) is an important raw material for the synthesis of fertilizers, nitric acid, ammonium salts, soda ash, etc., but the synthesis of ammonia is an industry with high energy consumption and low efficiency. Therefore, the development of new catalysts that can catalytically convert nitrogen (N2) and hydrogen (H2) into ammonia under mild conditions is one of the important topics in the field of synthetic ammonia.
[0003] Ru / C-based catalyst (ruthenium carbon catalyst) is a highly efficient catalyst with the advantages of high catalytic activity, good selectivity, fast reaction speed, mild reaction conditions, long service life and easy recovery. It is used in the industrial production of synthetic ammonia. However, when activated carbon is used as a carrier, problems such as methanation, metal sintering, loss of active components and poor mechanical strength are prone to occur in the process of synthetic ammonia, which restricts the further promotion and application of ruthenium-based ammonia synthesis catalyst. At present, the methanation of activated carbon is generally inhibited by adding promoters such as alkali metals, alkaline earth metals or rare earth metals to improve the performance of the catalyst; or by regulating the structural properties of the carbon-based carrier to better disperse Ru (ruthenium) nanoparticles and protect Ru nanoparticles from being sintered during the ammonia synthesis process. However, the above means not only increase the complexity of the process, but also have high costs.
[0004] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a method for preparing an ammonia synthesis catalyst and a method for synthesizing ammonia, aiming to improve the catalytic efficiency and stability of the ammonia synthesis catalyst and realize the synthesis of ammonia under low temperature and low pressure conditions.
[0006] In order to achieve the above objectives, this application adopts the following technical solutions:
[0007] The present application discloses a method for preparing an ammonia synthesis catalyst, the method comprising:
[0008] SiC (silicon carbide) is placed in a Joule heating device, evacuated, inert gas is introduced, and then thermal shock treatment is performed;
[0009] A certain amount of SiC after thermal shock treatment is weighed, ultrasonically dispersed, a certain amount of Ru precursor solution is added according to the loading amount of SiC, heated, stirred, and dried, and then the dried Ru / SiC composite is placed in a Joule heating device for thermal shock treatment to obtain a Ru / SiC catalyst for ammonia synthesis.
[0010] In some embodiments of the present application, the conditions of the SiC thermal shock treatment are 30V, 300A, 780-1000°C, and 5-50s.
[0011] In some embodiments of the present application, the inert gas introduced during the SiC thermal shock treatment is Ar or He.
[0012] In some embodiments of the present application, the solvent includes one of water, ethanol, methanol, cyclohexane, tetrahydrofuran or acetone.
[0013] In some embodiments of the present application, the Ru precursor solution includes one of ruthenium trichloride, ruthenium acetylacetonate, ruthenium nitrosonitrate, triruthenium dodecacarbonyl, and ruthenium acetate.
[0014] In some embodiments of the present application, the content of Ru in the catalyst is 0.3-5 wt %.
[0015] In some embodiments of the present application, the conditions for the thermal shock treatment of the Ru / SiC composite are 30V, 300A, 780-800°C, and 3-30s.
[0016] On the other hand, the present application also provides a method for synthesizing ammonia, wherein the method synthesizes ammonia by contacting hydrogen and nitrogen with the catalyst as described in any one of the above items.
[0017] In some embodiments of the present application, the hydrogen, the nitrogen and the catalyst are heated at a temperature of 200 to 500°C, a pressure of 0.1 to 5 MPa, and a space velocity of 1500 to 500000 h -1 The ammonia synthesis reaction is carried out under the conditions of.
[0018] Beneficial effects:
[0019] The present application provides a method for preparing an ammonia synthesis catalyst. The method adopts SiC, which is resistant to high temperature, acid and alkali corrosion, as a carrier, and uses a Joule heating device to create defects on the SiC surface, which is more conducive to the stable attachment of Ru particles to the carrier surface, can effectively improve the activity of the Ru / SiC catalyst in the ammonia synthesis reaction, and can inhibit metal sintering, extend the service life of the catalyst, and save costs; the preparation method has a simple process and low cost, and has potential industrial application prospects.
[0020] The method for synthesizing ammonia provided in the present application uses the above-mentioned Ru / SiC catalyst, and the efficiency of ammonia generation in the reaction is high, and the ammonia generation rate can be maintained in a stable range for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1Schematic diagram of ammonia generation rate in the ammonia synthesis reaction of the Ru / SiC catalyst prepared in Example 2 and Examples 4 to 6 provided in the present application. DETAILED DESCRIPTION
[0022] The present application provides a method for preparing an ammonia synthesis catalyst and a method for synthesizing ammonia. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail with reference to the accompanying drawings and examples. It should be understood that the specific examples described herein are only used to explain the present application and are not used to limit the present application.
[0023] The present application provides a method for preparing an ammonia synthesis catalyst, wherein SiC is used as a carrier and Ru is used as an active material.
[0024] SiC has the characteristics of high melting point, low density, low thermal expansion rate, etc., which enables SiC to provide good high temperature resistance, oxidation resistance and chemical inertness when used as a catalyst matrix, thereby enhancing the stability and durability of the catalyst. In addition, SiC has good compatibility with metal substrates, which can effectively enhance the mechanical strength and thermal stability of the metal substrate, thereby further improving the overall performance of the catalyst.
[0025] As an active substance of the catalyst, Ru can show extremely high activity in specific reactions, thus significantly accelerating the reaction rate, and has excellent stability. In addition, Ru is relatively cheap, cost-effective, and suitable for large-scale industrial applications.
[0026] Specifically, the preparation method comprises:
[0027] S001. Heat treatment of SiC: Take a certain amount of SiC sample, place the SiC sample in the sample slot of the Joule heating device, seal it, evacuate it with a vacuum pump for about 10 minutes, introduce inert gas, and then perform thermal shock treatment.
[0028] During the thermal shock treatment of SiC, the vacuum is evacuated for 10 minutes and an inert gas is introduced, which can completely exhaust the air in the Joule heating device, so that the heat treatment of SiC can be carried out in an inert gas atmosphere, preventing SiC from reacting with oxygen or other components in the air at high temperature, avoiding SiC oxidation or nitridation, and maintaining the purity and performance of the material.
[0029] Furthermore, the inert gas introduced during the SiC heat treatment overshoot may be selected from one of Ar (argon) and He (helium).
[0030] Ar and He have high chemical stability and hardly react with other elements. They are used as protective gases in SiC thermal reactions to ensure the purity of SiC and significantly improve thermal uniformity and efficiency. In addition, He has good thermal conductivity and extremely low density, which can promote efficient heat transfer inside the Joule heating device while ensuring good inert protection, improve energy efficiency, and reduce production costs.
[0031] The Joule heating device is easy to operate and has a fast heating speed. It can reach extremely high temperatures in a very short time, shortening the process time. In addition, the Joule heating device directly heats the sample tank through the Joule effect, reducing the loss during heat conduction, improving thermal efficiency, and reducing process costs to a certain extent. Furthermore, the Joule heating device controls the temperature by adjusting the current size and the current on and off time. It has high accuracy and can achieve rapid cooling, improving the controllability of the reaction.
[0032] Specifically, the SiC is thermally shocked for 5 to 50 seconds at a voltage of 30 V, a current of 300 A, and a temperature of 780 to 1000° C.
[0033] Under the above conditions, uniform defects can be produced on the surface of the SiC carrier, thereby facilitating more stable loading of Ru particles.
[0034] S200, Preparation of SiC-based Ru catalyst: Weigh a certain amount of SiC after thermal shock treatment, ultrasonically disperse it in a solvent, add a certain amount of Ru precursor solution according to the loading amount of SiC, heat, stir, and dry, and then place the dried Ru / SiC composite in a Joule heating device for thermal shock treatment to obtain a Ru / SiC catalyst for ammonia synthesis.
[0035] In the above, firstly dispersing SiC into the solvent by ultrasonic method and then adding the Ru precursor solution can accelerate the reaction rate and improve the uniformity of Ru loading on SiC, thereby improving the quality of Ru / SiC catalyst.
[0036] In some embodiments, the solvent for ultrasonically dispersing SiC can be one of water, ethanol, methanol, cyclohexane, tetrahydrofuran or acetone. Generally, SiC is substantially insoluble in water, ethanol, methanol, cyclohexane, tetrahydrofuran or acetone, and will not affect the loading of Ru onto the SiC surface. To ensure the purity of the product, water can be deionized water.
[0037] Generally, the amount of solvent used depends on the weight of the heat-treated SiC. For example, 995 mg of heat-treated SiC can be dispersed in 30 mL of solvent.
[0038] Specifically, after the Ru precursor solution is added to the above SiC solution, it is stirred and heated to 60°C for 4 hours to ensure that Ru can be fully loaded on the surface of SiC and precipitated. The reaction mixture is then rotary evaporated at 60°C and dried in a vacuum drying oven at 60°C overnight to ensure that the Ru / SiC composite can be completely dried and the quality of the obtained Ru / SiC catalyst is guaranteed.
[0039] The Ru precursor solution used for the Ru / SiC catalyst is not particularly limited, and may be ruthenium acetate, ruthenium carbonate, ruthenium nitrate, ruthenium ammonium salt, ruthenium citrate, ruthenium dinitrodiammonium salt, ruthenium complex, etc. Preferably, the Ru precursor solution may be selected from one of ruthenium trichloride, ruthenium acetylacetonate, ruthenium nitrosylnitrate, triruthenium dodecacarbonyl, and ruthenium acetate.
[0040] In addition, although the solvent used in the Ru precursor solution is not particularly limited, a solvent that can dissolve the above-mentioned ruthenium salt to form ruthenium ions can be used. Exemplarily, this solvent can be selected from tetrahydrofuran, water, alcohol, etc. In addition, the content of ruthenium salt in such a solution is not particularly limited, and according to the target ruthenium loading, it is only necessary to appropriately change the amount (volume, concentration, etc.) of the Ru precursor solution.
[0041] In some embodiments, the mass percentage content of Ru in the Ru / SiC catalyst may be 0.3-5wt%. That is, the mass percentage content of Ru in the Ru / SiC catalyst may be, but is not limited to, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 2.8%, 3%, 3.2%, 3.6%, 4%, 4.5%, 5%, etc.
[0042] Specifically, during the heat treatment of Ru / SiC, the thermal shock treatment may be performed at a voltage of 30 V, a current of 300 A, and a temperature of 780 to 800° C. for 3 to 30 seconds.
[0043] The thermal shock treatment under the above conditions enables Ru to be more stably attached to the SiC surface.
[0044] Another aspect of the present application provides a method for synthesizing ammonia, which uses hydrogen and nitrogen to contact the Ru / SiC catalyst prepared by the above method to carry out ammonia synthesis reaction under low temperature and low pressure conditions.
[0045] The above-mentioned ammonia synthesis method, using Ru / SiC catalyst, can realize the synthesis of ammonia under low temperature and low pressure conditions, reducing the energy consumption of the ammonia synthesis process, thereby improving the industrial efficiency of ammonia synthesis.
[0046] In some embodiments, hydrogen, nitrogen and catalyst can be heated at a temperature of 200 to 500° C., a pressure of 0.1 to 5 MPa, and a space velocity of 1500 to 500,000 h -1 The ammonia synthesis reaction is carried out under the conditions of.
[0047] Under the above conditions, the generation rate of ammonia is high, and the yield of ammonia can be stabilized in a high range for a relatively long period of time.
[0048] The present application will be described in more detail below through examples and comparative examples, but the present application is not limited to the following examples.
[0049] Example 1
[0050] 10 g of SiC was weighed and placed in a sample tank of a Joule heating device. After sealing, the sample was evacuated with a vacuum pump for 10 min, and then Ar gas was introduced. The sample was subjected to a thermal shock treatment at 30 V, 300 A, and 900 ° C for 20 s to obtain the heat-treated SiC.
[0051] Weigh 995 mg of the heat-treated SiC, ultrasonically disperse it in 30 mL of deionized water, add 4.95 mL of 0.01 mol / L ruthenium trichloride aqueous solution, stir and heat to 60 ° C in an oil bath for 4 hours; then dry the mixture at 60 ° C, and then place it in a vacuum drying oven at 60 ° C to dry overnight to obtain a Ru / SiC composite. Finally, place the completely dried Ru / SiC composite in a Joule heating device and perform high-temperature thermal shock treatment at 30V, 300A, and 780 ° C for 5s to obtain a Ru / SiC catalyst for synthetic ammonia. The Ru content in the catalyst is 0.5wt%.
[0052] The above catalyst was used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0053] 100 mg of the above Ru / SiC catalyst with a Ru content of 0.5 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixed gas with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. The temperature was 300°C, the pressure was 0.8 MPa, and the space velocity was 10000 h -1 The ammonia was synthesized under the conditions of catalysis. After the reaction was stable, the generation rate of ammonia in the tail gas at the outlet was detected to be 6.7mmolg -1 h -1 After 100 hours of continuous reaction, the activity of the catalyst can still be maintained at 94.5%.
[0054] Example 2
[0055] 10 g of SiC was weighed and placed in a sample tank of a Joule heating device. After sealing, the sample was evacuated with a vacuum pump for 10 min, and then Ar gas was introduced. The sample was subjected to a thermal shock treatment at 30 V, 300 A, and 900 ° C for 20 s to obtain the heat-treated SiC.
[0056] Weigh 995 mg of the heat-treated SiC, ultrasonically disperse it in 30 mL of ethanol, add 4.95 mL of 0.01 mol / L ruthenium acetylacetonate ethanol solution, stir and heat it in an oil bath to 60°C for 4 hours; then dry the mixture at 60°C by rotary evaporation, and then place it in a vacuum drying oven and dry it overnight at 60°C to obtain a Ru / SiC composite. Finally, place the completely dried Ru / SiC composite in a Joule heating device and perform high-temperature thermal shock treatment at 30V, 300A, and 780°C for 5s to obtain a Ru / SiC catalyst for synthetic ammonia. The Ru content in the catalyst is 0.5wt%.
[0057] The above catalyst was used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0058] 100 mg of the above Ru / SiC catalyst with a Ru content of 0.5 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixed gas with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. The temperature was 300°C, the pressure was 0.8 MPa, and the space velocity was 10000 h -1 The ammonia was synthesized under the conditions of catalysis. After the reaction was stable, the generation rate of ammonia in the tail gas at the outlet was detected to be 7.8mmolg -1 h -1 After 100 hours of continuous reaction, the activity of the catalyst can still be maintained at 91.3%.
[0059] Example 3
[0060] 10 g of SiC was weighed and placed in a sample tank of a Joule heating device. After sealing, the sample was evacuated with a vacuum pump for 10 min, and then Ar gas was introduced. The sample was subjected to a thermal shock treatment at 30 V, 300 A, and 900 ° C for 20 s to obtain the heat-treated SiC.
[0061] Weigh 995 mg of the heat-treated SiC, ultrasonically disperse it in 30 mL of tetrahydrofuran, add 1.65 mL of 0.01 mol / L tetrahydrofuran solution of triruthenium dodecacarbonyl, stir and heat it in an oil bath to 60°C for 4 hours; then, dry the mixture by rotary evaporation at 60°C, and then place it in a vacuum drying oven and dry it overnight at 60°C to obtain a Ru / SiC composite. Finally, place the completely dried Ru / SiC composite in a Joule heating device, and perform high-temperature thermal shock treatment at 30V, 300A, and 780°C for 5s to obtain a Ru / SiC catalyst for synthetic ammonia. The Ru content in the catalyst is 0.5wt%.
[0062] The above catalyst was used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0063] 100 mg of the above Ru / SiC catalyst with a Ru content of 0.5 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixed gas with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. The temperature was 300°C, the pressure was 0.8 MPa, and the space velocity was 10000 h -1 The ammonia was synthesized under the conditions of catalysis. After the reaction was stable, the generation rate of ammonia in the tail gas at the outlet was detected to be 4.2mmolg -1 h -1 After 100 hours of continuous reaction, the activity of the catalyst can still be maintained at 89.8%.
[0064] Example 4
[0065] 10 g of SiC was weighed and placed in a sample tank of a Joule heating device. After sealing, the sample was evacuated with a vacuum pump for 10 min, and then Ar gas was introduced. The sample was subjected to a thermal shock treatment at 30 V, 300 A, and 900 ° C for 20 s to obtain the heat-treated SiC.
[0066] Weigh 995 mg of the heat-treated SiC, ultrasonically disperse it in 30 mL of ethanol, add 14.85 mL of 0.01 mol / L ruthenium acetylacetonate ethanol solution, stir and heat it in an oil bath to 60°C for 4 hours; then dry the mixture at 60°C by rotary evaporation, and then place it in a vacuum drying oven and dry it overnight at 60°C to obtain a Ru / SiC composite. Finally, place the completely dried Ru / SiC composite in a Joule heating device and perform high-temperature thermal shock treatment at 30V, 300A, and 780°C for 5s to obtain a Ru / SiC catalyst for synthetic ammonia. The Ru content in the catalyst is 1.5wt%.
[0067] The above catalyst was used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0068] 100 mg of the above Ru / SiC catalyst with a Ru content of 1.5 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixed gas with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. The temperature was 300°C, the pressure was 0.8 MPa, and the space velocity was 10000 h -1 The ammonia was synthesized under the conditions of catalysis. After the reaction was stable, the generation rate of ammonia in the tail gas at the outlet was detected to be 9.0mmolg -1 h -1 After 100 hours of continuous reaction, the activity of the catalyst can still be maintained at 90.8%.
[0069] Example 5
[0070] 10 g of SiC was weighed and placed in a sample tank of a Joule heating device. After sealing, it was evacuated with a vacuum pump for 10 min, and then Ar gas was introduced. Thermal shock treatment was performed at 30 V, 300 A, and 900 ° C for 20 s to obtain heat-treated SiC.
[0071] Weigh 995 mg of the heat-treated SiC, ultrasonically disperse it in 30 mL of ethanol, add 30.77 mL of 0.01 mol / L ruthenium acetylacetonate ethanol solution, stir and heat it in an oil bath to 60°C for 4 hours; then, dry the mixture by rotary evaporation at 60°C, and then place it in a vacuum drying oven and dry it overnight at 60°C to obtain a Ru / SiC composite. Finally, place the completely dried Ru / SiC composite in a Joule heating device, and perform high-temperature thermal shock treatment at 30V, 300A, and 780°C for 5s to obtain a Ru / SiC catalyst for synthetic ammonia. The Ru content in the catalyst is 3wt%.
[0072] The above catalyst was used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0073] 100 mg of the above Ru / SiC catalyst with a Ru content of 3 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixed gas with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. Ammonia was synthesized under the conditions of a temperature of 300°C, a pressure of 0.8 MPa, and a space velocity of 10000 h-1. After the reaction was stabilized, the generation rate of ammonia in the tail gas at the outlet was detected to be 12.3 mmol / g. -1 h -1 After 100 hours of continuous reaction, the activity of the catalyst can still be maintained at 91.5%.
[0074] Example 6
[0075] 10 g of SiC was weighed and placed in a sample tank of a Joule heating device. After sealing, it was evacuated with a vacuum pump for 10 min, and then Ar gas was introduced. Thermal shock treatment was performed at 30 V, 300 A, and 900 ° C for 20 s to obtain heat-treated SiC.
[0076] Weigh 995 mg of the heat-treated SiC, ultrasonically disperse it in 30 mL of ethanol, add 52.37 mL of 0.01 mol / L ruthenium acetylacetonate ethanol solution, stir and heat it in an oil bath to 60°C for 4 hours; then dry the mixture at 60°C by rotary evaporation, and then place it in a vacuum drying oven and dry it overnight at 60°C to obtain a Ru / SiC composite. Finally, place the completely dried Ru / SiC composite in a Joule heating device and perform high-temperature thermal shock treatment at 30V, 300A, and 780°C for 5s to obtain a Ru / SiC catalyst for synthetic ammonia. The Ru content in the catalyst is 5wt%.
[0077] The above catalyst was used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0078] 100 mg of the above Ru / SiC catalyst with a Ru content of 5 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixed gas with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. Ammonia was synthesized under the conditions of a temperature of 300°C, a pressure of 0.8 MPa, and a space velocity of 10000 h-1. After the reaction was stabilized, the generation rate of ammonia in the tail gas at the outlet was detected to be 5.8 mmol / g. -1 h -1 After 100 hours of continuous reaction, the activity of the catalyst can still maintain 88.1% of Comparative Example 1
[0079] 995 mg of unheat-treated SiC was weighed, ultrasonically dispersed in 30 mL of deionized water, 4.95 mL of 0.01 mol / L ruthenium trichloride aqueous solution was added, and stirred and heated to 60°C in an oil bath for 4 hours; then the mixture was dried by rotary evaporation at 60°C, and then placed in a vacuum drying oven at 60°C for overnight to obtain a Ru / SiC composite. Finally, the completely dried Ru / SiC composite was placed in a Joule heating device and subjected to high-temperature thermal shock treatment at 30V, 300A, and 780°C for 5s to obtain a Ru / SiC catalyst for synthetic ammonia. The Ru content in the catalyst was 0.5wt%.
[0080] The above catalyst was used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0081] 100 mg of the above Ru / SiC catalyst with a Ru content of 0.5 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixture with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. Ammonia was synthesized under the conditions of a temperature of 300°C, a pressure of 0.8 MPa, and a space velocity of 10000 h-1. After the reaction was stabilized, the generation rate of ammonia in the tail gas at the outlet was detected to be only 0.4 mmol / g. -1 h -1 .
[0082] Comparative Example 2
[0083] 10 g of SiC was weighed and placed in a sample tank of a Joule heating device. After sealing, the sample was evacuated with a vacuum pump for 10 min, and then Ar gas was introduced. The sample was subjected to a thermal shock treatment at 30 V, 300 A, and 900 ° C for 20 s to obtain the heat-treated SiC.
[0084] 995 mg of the heat-treated SiC was weighed, ultrasonically dispersed in 30 mL of deionized water, 4.95 mL of 0.01 mol / L ruthenium trichloride aqueous solution was added, and the mixture was stirred and heated to 60° C. in an oil bath for 4 hours; then the mixture was dried by rotary evaporation at 60° C., and then dried in a vacuum drying oven at 60° C. overnight to obtain a Ru / SiC catalyst for synthesizing ammonia. The Ru content in the catalyst was 0.5 wt%.
[0085] The Ru / SiC catalyst which has not been thermally shocked by the Joule heating device is used to evaluate its ammonia synthesis performance on a fixed bed. The specific operation is as follows:
[0086] 100 mg of the above Ru / SiC catalyst with a Ru content of 0.5 wt% was loaded into a fixed bed reactor, and a hydrogen-nitrogen mixed gas with a molar ratio of hydrogen to nitrogen of 1:3 was introduced. The temperature was 300°C, the pressure was 0.8 MPa, and the space velocity was 10000 h -1 The ammonia was synthesized under the conditions of catalysis. After the reaction was stable, the generation rate of ammonia in the tail gas at the outlet was detected to be 2.3mmolg -1 h -1 After 30 hours of continuous reaction, the activity of the catalyst can still be maintained at 32.8%.
[0087] The performance evaluation results of the ammonia synthesis catalysts obtained in Examples 1 to 6 and Comparative Examples 1 and 2 are shown in Table 1.
[0088] Table 1
[0089]
[0090]
[0091] It can be seen from the above Examples 1 to 6 and Table 1 that in the evaluation of the synthetic ammonia performance of the Ru / SiC catalyst prepared by the preparation method described in the present application, the Ru / SiC catalyst with a Ru content of 0.5 wt% can generate ammonia at a rate of up to 7.8 mmol / g -1 h -1 The activity of the catalyst can be maintained at about 90% after 100 hours of reaction. The Ru / SiC catalyst with a Ru content of 3 wt% can generate ammonia at a rate of up to 12.3 mmol / g -1 h -1 ; and after 100 hours of reaction, the activity of the catalyst can still be maintained at about 90%. Therefore, the catalyst prepared by the method described in the present application has good ammonia generation efficiency when applied to ammonia synthesis reaction, and has a long service life and high industrial benefits.
[0092] Figure 1Schematic diagram of ammonia generation rate in the ammonia synthesis reaction of the Ru / SiC catalyst prepared in Example 2 and Examples 4 to 6 provided in the present application.
[0093] From Examples 2, 4 to 6 and Table 1, Figure 1 It can be seen that when the Ru loading is not higher than 3wt%, the ammonia generation rate gradually increases with the increase of Ru loading; when the Ru loading is greater than 3wt%, the ammonia generation rate gradually decreases. Therefore, controlling the Ru content in the catalyst to be no higher than 5wt% not only ensures the ammonia generation rate of the catalyst in the ammonia synthesis reaction, but also ensures cost-effectiveness.
[0094] It can be seen from Example 1, Comparative Example 1, Comparative Example 2 and Table 1 that, compared with Example 1, Comparative Example 1 lacks the heat treatment of SiC, and the ammonia generation rate of the catalyst prepared therefrom is only 0.4 mmol / g in the performance evaluation of synthetic ammonia. -1 h -1 Comparative Example 2 Compared with Example 1, the dried Ru / SiC catalyst was not subjected to the Joule heating device thermal shock treatment. In the evaluation of synthetic ammonia performance, the ammonia generation rate of the prepared catalyst was only 2.3 mmol / g -1 h -1 After 30 hours of continuous reaction, the activity of the catalyst can still be maintained at 32.8%. It can be seen that the thermal shock treatment of SiC and Ru / SiC catalysts by Joule heating device can greatly improve the catalytic efficiency of Ru / SiC catalyst in the ammonia synthesis reaction, increase the generation rate of ammonia, and greatly extend the service life of Ru / SiC catalyst.
[0095] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and application concept of the present application, and all these changes or substitutions should fall within the protection scope of the claims attached to the present application.
Claims
1. A method for preparing an ammonia synthesis catalyst, characterized in that: include: SiC is placed in a Joule heating device, evacuated, introduced with inert gas, and then subjected to thermal shock treatment; A certain amount of SiC after thermal shock treatment is weighed and ultrasonically dispersed in a solvent, a certain amount of Ru precursor solution is added according to the loading amount of SiC, heated, stirred and dried, and then the dried Ru / SiC composite is placed in a Joule heating device for thermal shock treatment to obtain a Ru / SiC catalyst for ammonia synthesis.
2. The method for preparing an ammonia synthesis catalyst according to claim 1, characterized in that: The conditions of the SiC thermal shock treatment are 30V, 300A, 780-1000°C, and 5-50s.
3. The method for preparing an ammonia synthesis catalyst according to claim 1, characterized in that: The inert gas introduced during the SiC thermal shock treatment is Ar or He.
4. The method for preparing an ammonia synthesis catalyst according to claim 1, characterized in that: The solvent includes one of water, ethanol, methanol, cyclohexane, tetrahydrofuran or acetone.
5. The method for preparing an ammonia synthesis catalyst according to claim 1, characterized in that: The Ru precursor solution includes one of ruthenium trichloride, ruthenium acetylacetonate, ruthenium nitrosyl nitrate, triruthenium dodecacarbonyl, and ruthenium acetate.
6. The method for preparing an ammonia synthesis catalyst according to claim 1, characterized in that: The content of Ru in the catalyst is 0.3-5 wt%.
7. The method for preparing an ammonia synthesis catalyst according to claim 1, characterized in that: The conditions for the thermal shock treatment of the Ru / SiC composite are 30V, 300A, 780-800°C, and 3-30s.
8. A method for synthesizing ammonia, characterized in that: Ammonia is synthesized by contacting hydrogen and nitrogen with the catalyst according to any one of claims 1 to 7.
9. The method for synthesizing ammonia according to claim 8, characterized in that: The hydrogen, nitrogen and catalyst are heated at a temperature of 200 to 500° C., a pressure of 0.1 to 5 MPa, and a space velocity of 1500 to 500000 h / min. -1 The ammonia synthesis reaction is carried out under the conditions of.
Citation Information
Cited By
Carbon-containing molecular sieve catalyst loaded with high-dispersion active metal as well as preparation method and application of carbon-containing molecular sieve catalyst
CN120532536A
Ruthenium-based ammonia synthesis catalyst based on high-entropy oxide carrier as well as preparation and application of ruthenium-based ammonia synthesis catalyst
CN121669226A
Ruthenium-based ammonia synthesis catalysts based on high-entropy oxide supports and preparation and use thereof
CN121669226B
